Daptomycin Inhibits Multiple Myeloma Progression through Downregulating the Expression of RPS19 - Zhuang, Yijun; Zhang, Yin; Chen, Caiyun; Chen, Jincheng; Xu, Qiuxia; Wang, Peihong (Combinatorial Chemistry & High Throughput Screening, 2025)
ObjectivesThis study aimed to explore new therapeutic drugs for multiple myeloma (MM). MM is a common plasma cell malignant proliferative disease, accounting for 15% of hematological malignancies. The role of daptomycin (DAP), a potential anti-tumor drug, remains unclear in MM. In the present research, we investigated the anticancer effect of DAP in MM cell line RPMI 8226.MethodsRPMI 8226 cells were treated with DAP (20 μM, 40 μM, and 80 μM) with 20 nM bortezomib (BZ) as a positive control. Cell function was detected using CCK8, flow cytometry, and transwell assay.ResultsIn MM cells, DAP inhibited proliferation and induced apoptosis. The cell cycle was arrested at the G1 phase after the treatment of DAP. The migration and invasion abilities were also inhibited by DAP treatment in RPMI 8226 cells. Importantly, the mRNA and protein levels of RPS19 were downregulated in DAP-treated RPMI 8226 cells.ConclusionDAP inhibited the proliferation, migration, and invasion and promoted the apoptosis of MM cells. Mechanistically, the RPS19 expression was significantly decreased in DAP-treated cells. This research provides a potential therapeutic drug for MM therapy.
Keywords: RPS19